Clinical and Radiographic Outcomes After Surgical Treatment of Proximal Humeral Fractures with Head-Split Component. (2nd January 2020) - Peters, Paulina-Maria; Plachel, Fabian; Danzinger, Victor; Novi, Michele; Märdian, Sven; Scheibel, Markus; Moroder, Philipp
Abstract : Background: Head-split fractures are a subgroup of proximal humeral fractures in which the fracture line affects the articular surface. Limited data are available regarding outcomes and risk factors for failure following surgical treatment of this rare fracture type. Methods: Of 45 patients with head-split fractures identified, a total of 30 (67%) were included in this retrospective study, with a mean follow-up of 49 ± 18 months (range, 12 to 83 months). Of those 30, 24 were treated with open reduction and internal fixation (ORIF), 4 with reverse total shoulder arthroplasty (RTSA), and 2 with hemiarthroplasty. Subjective Shoulder Value, Simple Shoulder Test, Constant score, and biplanar radiographs were assessed. Fracture pattern, quality of reduction, eventual complications, revision procedures, and clinical failure (adjusted Constant score < 40) were analyzed, and risk factors for failure were calculated. Results: The overall complication rate was 83% (ORIF: 21 of 24 [88%]; RTSA: 3 of 4 [75%]; and hemiarthroplasty: 1 of 2 [50%]). The most common complications following ORIF were humeral head osteonecrosis (42%), malunion of the lesser tuberosity (33%), and screw protrusion (29%), whereas all complications following RTSA were related to tuberosity problems. Revision was performed in 7 of 24 (29%) of initial ORIF patients, and no revisions were performed in RTSA or hemiarthroplasty patients. Four patients (17%) who underwent primary ORIF underwent conversion to RTSA, and 3 patients (12.5%) had screw removal due to penetration. The overall clinical failure rate was 50% (ORIF: 12 of 24 [50%]; RTSA: 1 of 4 [25%]; and hemiarthroplasty: 2 of 2 [100%]). No significant association was found between preoperative factors and clinical failure. ORIF and primary RTSA showed higher average clinical outcome scores than primary hemiarthroplasty and secondary RTSA. In general, patients who required revision had worse Subjective Shoulder Value (p = 0.014), Simple Shoulder Test (p = 0.028), and adjusted Constant scores (p = 0.069). Conclusions: Head-split fractures of the humerus treated with ORIF showed high complication and revision rates. RTSA resulted in comparable clinical outcomes and complication rates; however, the complications associated with RTSA were mostly related to tuberosity problems, which in this small series did not require revision. Therefore, RTSA may be the most predictable treatment option for head-split fractures in elderly patients. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete list of levels of evidence.